Lessons from the pandemic: Relationship between patient visits and patient length of stay in California’s health system - David D. Cho; Yu Wang (Health Research Policy and Systems)
Abstract Background The coronavirus disease 2019 (COVID-19) pandemic placed a heavy strain on the United States healthcare system. Common hospital operational performances were impacted to varying degrees by the pandemic. This study examined the healthcare operational measures during COVID-19 pandemic. Methods This cross-sectional study examined the COVID-19 cases and death counts of 56 California counties and hospital-level utilization data of 397 hospitals in California from January 2019 to March 2021. Results A total of 56 California counties were analysed, of which 37 counties were urban and 19 counties were rural. Average patient length of stay was positively associated with the number of intensive care unit visits by COVID-19 patients for all counties, as well as urban and rural counties separately. However, average patient length of stay was negatively associated with the number of inpatient visits by COVID-19 patients for all counties and urban counties. Conclusions The findings suggest that, while the need for additional beds and nursing staff in intensive care units exceeded initial estimates, there were also opportunities to streamline the care process for improved efficiency in regular acute care units. The understanding of factors impacting average patient length of stay would be valuable for hospital administrators in optimizing resource allocation and utilization to balance patient outcomes with financial sustainability during disruptive events.